Women as constitution-makers case studies from the new democratic era - Rubio-Marín, Ruth 1969-; Irving, Helen (Cambridge University Press, 2019)
"That a constitution should express the will of 'the people' is a long-standing principle, but the identity of 'the people' has historically been narrow. Women, in particular, were not included. A shift, however, has recently occurred. Women's participation in constitution-making is now recognised as a democratic right. Women's demands to have their voices heard in both the processes of constitution-making and the text of their country's constitution, are gaining recognition. Campaigning for inclusion in their country's constitution-making, women have adopted innovative strategies to express their constitutional aspirations. This collection offers, for the first time, comprehensive case-studies of women's campaigns for constitutional equality in nine different countries that have undergone constitutional transformations in the 'participatory era.' Against a richly-contextualised historical and political background, each charts the actions and strategies of women participants, both formal and informal, and records their successes, failures and continuing hopes for constitutional equality"...